Form of Social and Environmental Responsibility in PT. Asian Agri Company (Palm Oil Factory in Tanah Datar Village, Asahan Regency) - Tarigan, Indra Jaya Sakti; Maswandi, Maswandi; Rafiqi, Rafiqi (Journal of Public Representative and Society Provision, 2025)
This study examines the implementation of Corporate Social Responsibility (CSR) by PT. Asian Agri, especially at the Palm Oil Mill in Tanah Datar Village, Asahan Regency, in the context of Government Regulation Number 47 of 2012. The study uses a normative and empirical juridical approach through analysis of laws and regulations, field observations, and in-depth interviews with the company, local communities, and village governments. The results of the study indicate that PT. Asian Agri has implemented various CSR programs that include liquid and solid waste management, community empowerment, and environmental conservation. This program has a positive impact in the form of reducing environmental pollution, increasing community welfare, and supporting sustainable development. However, challenges in terms of technology investment costs and community environmental awareness are still obstacles. Therefore, the study recommends increasing collaboration between companies, governments, and communities to optimize the impact of CSR and stricter regulatory oversight for program sustainability.